Economic Evaluation of the Use of Cefotaxime and Ceftazidime in the Treatment of Pneumonia in Pediatric Patients - Valen Ruterlin; Rano K. Sinuraya; Eli Halimah; Melisa I. Barliana; Sri Hartini (Universitas Padjadjaran, 2017)
The prevalence of pneumonia is particularly high among pediatric patients. Appropriate antibiotics selection is required to reduce mortality and morbidity rates associated with these diseases. However, information on cost-effectiveness of empirical antibiotics treatment for pneumonia was limited. This study was aimed to evaluate cost-effectiveness of cefotaxime and ceftazidime for pneumonia in pediatric patients. This study was a retrospective cross sectional study conducted at a hospital in Bandung during January-December 2012. Data were derived from medical records of pediatric pneumonia inpatients during study period. Cost was calculated based on direct medical cost, i.e., inpatient care, medical support, and medicines that were used from admission until hospital discharge. The results showed that there was no statistical difference in the average medical cost of the treatment using cefotaxime (1,197,017 IDR) and ceftazidime (2,245,748 IDR). Incremental cost effectiveness ratio (ICER) showed that cefotaxime is more cost effective than ceftazidime with greater reduction of leukocytes level (576 IDR/mm3 ). The use of cefotaxime is recommended for the treatment of pnuemonia in pediatric patients. Keywords: cost minimization, cost effectiveness, cefotaxime, ceftazidime, pneumonia